2006
DOI: 10.1530/rep.1.01224
|View full text |Cite
|
Sign up to set email alerts
|

NuMA distribution and microtubule configuration in rabbit oocytes and cloned embryos

Abstract: The assembly of microtubules and the distribution of NuMA were analyzed in rabbit oocytes and early cloned embryos. a-Tubulin was localized around the periphery of the germinal vesicle (GV). After germinal vesicle breakdown (GVBD), multi-arrayed microtubules were found tightly associated with the condensed chromosomes and assembled into spindles. After the enucleated oocyte was fused with a fibroblast, microtubules were observed around the introduced nucleus in most reconstructed embryos and formed a transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Remarkably, the function of NuMa in tethering microtubule minus ends is conserved in acentriolar spindles. Indeed, the microtubule-associated protein NuMa accumulates at the poles in rabbit, human, and mouse oocytes (Yan et al, 2006;Alvarez Sedó et al, 2011;Kolano et al, 2012). In mouse oocytes, NuMa is required for the formation of barrel-shaped spindle poles as well as microtubule minus-end cohesion (Fig.…”
Section: Spindle Pole Formationmentioning
confidence: 99%
“…Remarkably, the function of NuMa in tethering microtubule minus ends is conserved in acentriolar spindles. Indeed, the microtubule-associated protein NuMa accumulates at the poles in rabbit, human, and mouse oocytes (Yan et al, 2006;Alvarez Sedó et al, 2011;Kolano et al, 2012). In mouse oocytes, NuMa is required for the formation of barrel-shaped spindle poles as well as microtubule minus-end cohesion (Fig.…”
Section: Spindle Pole Formationmentioning
confidence: 99%
“…1992); however, when somatic cells were introduced by NT, the majority of embryos had abnormal PCC configurations (Chesne et al. 2002; Yan et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit, after fusing a somatic nucleus with a mature oocyte, the cloned construct undergoes maturation-promoting factor activation, nuclear membrane breakdown, chromosome condensation and the formation of a metaphase spindle-like structure. When early-stage embryo blastomeres at G0 ⁄ G1 phase were used as donor cells, metaphase chromosomes and spindle were intact in most cases of PCC (Collas et al 1992); however, when somatic cells were introduced by NT, the majority of embryos had abnormal PCC configurations (Chesne et al 2002;Yan et al 2006). Similar to the previous results, our data showed that most of the somatic cell nuclei would undergo PCC 1 h post-fusion with nonactivated enucleated oocytes and chromosomes in most cases misaligned with the spindle or individual chromosomes located near the spindle poles regardless of which donor cell we used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations